2009
DOI: 10.1111/j.1600-0609.2009.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of real‐time PCR technique in the detection of novel protein 4.2 gene mutations that coexist with thalassaemia alpha in a single patient

Abstract: α-Thalassaemia is a very rare disease in Northern Europe in contrast to hereditary spherocytosis that is associated with red blood cell membrane defects. We report here α-thalassaemia case who was also found to bear the erythrocyte membrane protein 4.2 gene mutations. mRNA relative quantification of red cell membrane protein genes in a Polish patient with α-thalassaemia trait indicated EPB42 as the gene that could also be involved in anaemia pathogenesis. Sequencing revealed the presence of two novel mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…By conducting genomic DNA sequencing, they found a homozygous mutation, 1747G>T, in exon 11 of EPB42 , and the proband’s mother was heterozygous for mutations. Maciag et al [43] observed that the relative mRNA levels of EPB42 were decreased by approximately 45% in a Polish α-thalassemia patient with a protein 4.2 mutation. They identified 2 mutations by sequencing: G1701A in exon 10 EPB42 , leading to an A567T mutation, and IVS2nt+6T>A in EPB42 , decreasing splice site activity and leading to mRNA instability.…”
Section: Molecular Genetic Mechanisms Of Five Hs-related Genesmentioning
confidence: 99%
“…By conducting genomic DNA sequencing, they found a homozygous mutation, 1747G>T, in exon 11 of EPB42 , and the proband’s mother was heterozygous for mutations. Maciag et al [43] observed that the relative mRNA levels of EPB42 were decreased by approximately 45% in a Polish α-thalassemia patient with a protein 4.2 mutation. They identified 2 mutations by sequencing: G1701A in exon 10 EPB42 , leading to an A567T mutation, and IVS2nt+6T>A in EPB42 , decreasing splice site activity and leading to mRNA instability.…”
Section: Molecular Genetic Mechanisms Of Five Hs-related Genesmentioning
confidence: 99%
“…At present, SDS-PAGE is commonly used to analyse membrane proteins, however it is not sensitive to HS patients or asymptomatic patients. Compared with SDS-PAGE, quantitative fluorescence real-time PCR has a higher sensitivity and specificity, and direct sequencing can identify mutation sites of HS after extracting genomic DNA and conducting PCR ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%